Electrical Discharge Machining pulse power generator to machine micropits of hip implant - Nazriah, Mahmud; Azli, Yahya; Mohammed Rafiq, Abdul Kadir; Syahrullail, Samion; Nor Liyana, Safura Hashim (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/